Early Reading through Storytelling Activities - Kristi Nuraini (Universitas Ahmad Dahlan, 2020)
Storytelling has been a part of childrenâ€™s life. They loved being told as well as telling a story. Being told a story made them see what has been read, and telling a story made them talk as they spoke it out. As the children learn a language, story is one effective way for them to learn a language. This study is aimed to find out to what extent storytelling could help young children with their early reading comprehension in terms of story-retell.Â One class in one national plus school has been the setting of the study with 13 students as the subjects. A mix method was implemented through a classroom action research design. This study came up with a significant result that storytelling activities have been effective ways to increase young childrenâ€™s retell fluency, both in content and fluency. The help of pictures, cue cards, and flashcards has been very efficient in helping young children to have a better comprehension in their early reading. These teaching aids had also been able to motivate them to be more active and engaged during the class.